2011
DOI: 10.1128/iai.01024-10
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactive Protection against Enterohemorrhagic Escherichia coli Infection by Enteropathogenic E. coli in a Mouse Model

Abstract: Enteropathogenic Escherichia coli (EPEC) and enterohemorrhagic E. coli (EHEC) are related attaching and effacing (A/E) pathogens. The genes responsible for the A/E pathology are carried on a chromosomal pathogenicity island termed the locus of enterocyte effacement (LEE). Both pathogens share a high degree of homology in the LEE and additional O islands. EHEC prevalence is much lower in areas where EPEC is endemic. This may be due to the development of antibodies against common EPEC and EHEC antigens. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…In fact, intragastric immunization with a clinical isolate EPEC O126:H6 and challenge using the EHEC O157:H7 wild-type strain yielded sick mice, but with no dead mice reported. Interestingly, it was also shown that the EspB and intimin antibodies produced after the EPEC vaccination were cross-reactive against EspB (translocated protein and effector that prevents phagocytosis) and intimin from EHEC (Calderon Toledo et al, 2011 ).…”
Section: Development Of Vaccines Against Ehecmentioning
confidence: 99%
“…In fact, intragastric immunization with a clinical isolate EPEC O126:H6 and challenge using the EHEC O157:H7 wild-type strain yielded sick mice, but with no dead mice reported. Interestingly, it was also shown that the EspB and intimin antibodies produced after the EPEC vaccination were cross-reactive against EspB (translocated protein and effector that prevents phagocytosis) and intimin from EHEC (Calderon Toledo et al, 2011 ).…”
Section: Development Of Vaccines Against Ehecmentioning
confidence: 99%
“…Although mice do not developed the symptoms associated with diarrheal disease observed in humans, development of murine models of E. coli O157:H7 infection, including axenic (no indigenous intestinal flora) or streptomycin-treated Balb/c (reduced normal flora) mice have proved to be useful for EHEC colonization and candidate vaccine testing [20]. Because the lack of a naturally EHEC infected mouse model is a major obstacle, the ability of Citrobacter rodentium to naturally colonize and form A/E lesions in mice has been explored as a alternative for A/E pathogens-mediated disease and could be used for vaccine evaluation [54]. As such, a new Stx-expressing C. rodentium strain has been developed to resemble EHEC infection in mice [55].…”
Section: Small Animal Modelsmentioning
confidence: 99%
“…EPEC, characterized by their pathogenic phenotype and subsequent inflammatory response, is a chief etiology of diarrhea and intestinal inflammation in human beings. EPEC infection in cultured IEC has been shown to induce attaching‐and‐effacing (A/E) lesions . To our knowledge, the regulation of EPEC on autophagy in IEC has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%